Enduro World Series (EWS) mountain biking injuries: A 2-year prospective study of 2010 riders - Palmer, D.; Florida-James, G.; Ball, C. (International Journal of Sports Medicine, 2021)
The sport of Enduro is the newest International Cycling Union sanctioned discipline in mountain biking. There are a number of studies reporting mountain biking injury to date however there are none detailing injuries in Enduro. The aim of the present study was to determine the rate, severity and nature of rider injury during the Enduro World Series. Rider injury, and race and practice exposure data were recorded prospectively during 10 events across the 2017 and 2018 seasons. Incorporating 2010 riders (males 90%; females 10%) from 46 countries. 8.9% of riders were injured with mean 12.3 days time-loss per injury. Racing injury incidence was 38.3/1000 hours and practice injury incidence 3.6/1000 hours (p=0.01). The shoulder/clavicle (12.8% of all injuries), hand (9.0%) and head (9.0%) were the most injured locations. Concussion injury was the most frequent diagnosis (7.4%), and shoulder/clavicle fractures caused the greatest burden (442 total days lost). Of those with concussion 28.6% continued racing, and 42.9% reported no time-loss (i. e. time off) post-race. In conclusion, the rate of injury during EWS race events was comparable to Downhill racing. Targeted injury prevention strategies around rider concussion education and rider qualification criteria may help to reduce the risk of injury in Enduro.